Anti-obesity effect of Cydonia oblonga Miller extract in high-fat diet-induced obese C57BL/6 mice. (February 2022) - Lee, Hyun Sook; Jeon, Young Eun; Jung, Jae In; Kim, So Mi; Hong, Su Hee; Lee, Jaehak; Hwang, Jung Soon; Hwang, Myeong Oh; Kwon, Kisung; Kim, Eun Ji
Graphical abstract: Highlights: Cydonia oblonga Miller extract (COME) exerts anti-obesity effect in obese mouse. COME reduces white adipose tissue deposition in high-fat diet induced obese mice. COME induces the activation of AMPK in epididymal adipose tissue. COME modulates adipogenic transcription factors and their target genes expressions. Abstract: The present study was designed to explore whether Cydonia oblonga Miller extract (COME) had anti-obesity effects and the mechanism involved. COME reduced body weight, fat mass, adipose tissue weight, and serum levels of insulin, triglyceride, and leptin, but increased the serum levels of adiponectin and high-density lipoprotein-cholesterol in high-fat diet (HFD)-induced obese C57BL/6 mice. COME increased AMPK activation. COME suppressed adipogenesis by decreasing CCAAT/enhancer binding protein α, peroxisome proliferator-activated receptor γ, sterol regulatory element-binding protein-1c, acetyl-CoA carboxylase 1, ATP-citrate lyase, fatty acid synthase, and adipocyte protein 2 mRNA expression and enhanced lipolysis by increasing carnitine palmitoyl transferase 1 and hormone sensitive lipase mRNA expression. These results suggest that COME is potentially beneficial in inhibiting HFD-induced obesity by inducing AMPK activation and thereby, regulating several pathways involved in inhibiting adipogenesis, and promoting lipolysis and fatty acid oxidation. Our results suggest that COM may be used as an anti-obesity agent.